Nghiên cứu sự tạo phức và hoạt tính xúc tác của phức Co(II) với axit Citric (H4L) trong hệ: H2O-Co(II)–axit xitric (H4L)–Indigocarmin (IND)–H2O - Dưỡng và cộng sự, Nguyễn Văn (Vietnam Journal of Chemistry, 2014)
This article presents the results of complex formation of Co2+ with citric acid (H4L). The formed mononuclear complexes [Co(L)]2-have been used as catalysts for reactions of Indigocarmine (Ind) oxidation by H2O2 in the systems: H2O-Co2+-H4L-Ind-H2O2 (1)